2000
DOI: 10.1128/jvi.74.17.7922-7935.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Epitope Mapping of Neutralizing Monoclonal Antibodies Produced by Immunization with Oligomeric Simian Immunodeficiency Virus Envelope Protein

Abstract: In an attempt to generate broadly cross-reactive, neutralizing monoclonal antibodies (MAbs) to simian immunodeficiency virus (SIV), we compared two immunization protocols using different preparations of oligomeric SIV envelope (Env) glycoproteins. In the first protocol, mice were immunized with soluble gp140 (sgp140) from CP-MAC, a laboratory-adapted variant of SIVmacBK28. Hybridomas were screened by enzymelinked immunosorbent assay, and a panel of 65 MAbs that recognized epitopes throughout the Env protein wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 89 publications
2
76
0
Order By: Relevance
“…The V1, V2 and V4 Env variable loops can also serve as targets for neutralizing antibodies to HIV-1 Env [97][98][99][100][101][102]. Similar to the V3 loop antibody repertoire, many of the V1, V2 and V4 specifities of induced antibodies are strain specific.…”
Section: Antibody Escape and Evasion Mechanisms Of Hiv-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The V1, V2 and V4 Env variable loops can also serve as targets for neutralizing antibodies to HIV-1 Env [97][98][99][100][101][102]. Similar to the V3 loop antibody repertoire, many of the V1, V2 and V4 specifities of induced antibodies are strain specific.…”
Section: Antibody Escape and Evasion Mechanisms Of Hiv-1mentioning
confidence: 99%
“…However, one goal of vaccine development is to find antibody specificities that can bind to native Env trimers and induce the exposure of critical epitopes on the V3 loop. V3 immunogens that reflect conserved functional regions of the V3 loop would then become viable vaccine targets.The V1, V2 and V4 Env variable loops can also serve as targets for neutralizing antibodies to HIV-1 Env [97][98][99][100][101][102]. Similar to the V3 loop antibody repertoire, many of the V1, V2 and V4 specifities of induced antibodies are strain specific.…”
mentioning
confidence: 99%
“…Inoculations were performed by intradermal injections of 50 g of gp140-GCN4 in IFA three times with 1-wk intervals, with a final boost 3 days before the hybridoma fusion was performed. Splenocytes were harvested and fused with SP2 myeloma cells, as described (46). Hybridomas were screened by ELISA for gp120 binding and cloned by limiting dilution.…”
Section: Generation Of Hybridoma Cell Linesmentioning
confidence: 99%
“…One hypothesis is that neutralization sensitivity is related to the density of envelope spikes on the virion, requiring a threshold level of antibody binding to limit infectivity (27,(38)(39)(40). Alternatively, neutralization of virus by antibody has been associated with differences in the qualitative antibody binding properties, i.e., antibody affinity and epitope specificity (9,15,26,56). Previous studies have suggested a relationship between antibody affinity for oligomeric gp120 and neutralization of HIV-1 (19,44,46), and monoclonal antibodies (MAbs) that bind the V3 loop of diverse HIV-1 gp120 proteins with similar association rates exhibited marked differences in the dissociation rates that were predictive of neutralization capacity (48).…”
mentioning
confidence: 99%